Investigating entrepreneurship levels of pre-service music teachers - Rasim Erol Demirbatır (Intelektual Pustaka Media Utama, 2021)
The aim of this study was to examine the entrepreneurship levels of Pre-Service Music Teachers (Bursa Uludağ University Faculty of Education Music Teaching Undergraduate Program students) in terms of gender, grade level and career goals. For this purpose, data were collected from all 1st and 4th year students studying at Bursa Uludağ University Faculty of Education, Department of Music Education. The Individual Entrepreneurship Perception Scale (IEPS) and a Personal Information Form were used to collect the data. Mann Whitney U test was used to analyze the data. In line with the findings obtained, it was found that there was no significant difference in terms of IEPS total and subscale scores by gender. However, there were significant differences in favor of 4th year students in terms of locus of control, self-confidence and self-discipline sub-scores, as well as the total IEPS scores by grade level. It was concluded that those aiming for a non-teaching profession got significantly higher locus of control scores than those aiming to become a teacher. Regarding these results, suggestions have been developed to increase the entrepreneurship level of pre-service music teachers.